Estudo comparativo das assembleias de ascidias em duas regiões portuárias da costa brasileira - Paiva, Amarilis Brandão de (2013)
The intensification of the maritime transport around the world is coupled with an increase in the harbors and dockings infrastructure. These structures provide hard substrata for a generally abundant and diverse encrusting fauna. It has been demonstrated that artificial substrata in ports and marinas may harbor a considerable amount of exotic species. Ascidians are among the most important groups in such environments, being transported in the hulls or ballast water of ships connecting different regions. The present study investigate the assemblage of ascidians encrusting settling plates in two different harbor areas, distant more than 20º of latitude along the Brazilian coast. The polystyrene settling plates measured 12 x 12 cm were arranged in pairs, forming a “sandwich” with a 2cm space between them, and were kept submerged for periods of three months and one year, while the experiment lasted two years. The species richness of both areas was just slightly different (33 species in Ceará and 31 in São Paulo). On the other hand, Ceará presented a larger species richness per plate than São Paulo. In São Paulo, at the limit of the tropics, a stronger influence of seasonality was detected in terms of species composition between different periods. The compositions of the assemblages from the plates submerged for three months and one year was also different. The assemblage recruiting the internal and external faces of the plates sets were also different in terms of specific composition. The yearly plates presented a lower coverage of ascidians when compared to the quarterly plates, with a corresponding increase in coverage for other groups such as sponges and bryozoans. The internal faces of yearly plates showed a greater abundance of solitary ascidians, mainly Ascidia sydneiensis. The species Rhodosoma turcicum was recorded for the first time in the northern Brazilian coast. The presence of many exotic or cryptogenic species at the studied areas highlights the importance of continuous regular monitoring of the encrusting fauna in harbors and marinas.